A Terminal Iridium Oxo Complex with a Triplet Ground State. (3rd July 2019) - Delony, Daniel; Kinauer, Markus; Diefenbach, Martin; Demeshko, Serhiy; Würtele, Christian; Holthausen, Max C.; Schneider, Sven
Abstract: A terminal iridium oxo complex with an open‐shell ( S =1) ground state was isolated upon hydrogen atom transfer (HAT) from the respective iridium(II) hydroxide. Electronic structure examinations support large spin delocalization to the oxygen atom. Selected oxo transfer reactions indicate the ambiphilic reactivity of the iridium oxo moiety. Calorimetric and computational examinations of the HAT revealed a bond dissociation free energy for the IrO−H bond that is sufficient for hydrogen atom abstraction towards C−H bonds and small contributions from entropy and spin–orbit coupling to the HAT thermochemistry. Abstract : Ein terminaler Iridium(III)‐Oxo‐Komplex wurde isoliert und vollständig charakterisiert. Der ambiphile Oxo‐Komplex hat einen ungewöhnlichen Triplett‐Grundzustand und weist einen großen Sauerstoffradikalcharakter auf. Thermochemische Untersuchungen des entsprechenden Hydroxo/Oxo(Ir II OH/Ir III O)‐Paares zeigen, dass die Dissoziationsenergie der O‐H‐Bindung für die Aktivierung starker E‐H‐Bindungen ausreicht.